In vivo and in vitro therapeutic evaluation of bone marrow-derived mesenchymal stem cells in liver cancer treatment - Johor, Abdulrahman; Mahadiuzzaman, A. S. M.; Alqusayer, Abdulaziz Abdullah; Alkarim, Saleh Abdulaziz; Opo, F. A. Dain Md (Frontiers in Cell and Developmental Biology, 2025)
Hepatocellular carcinoma is the seventh most common kind of cancer worldwide and the second largest cause of cancer-related deaths in males, behind lung cancer. Globally, 866,000 people were diagnosed with hepatocellular carcinoma (HCC) in 2022, and nearly 42,240 new cases will be identified in 2025 in the United States. Using stem cells obtained from bone marrow can effectively reduce the number of malignant tumor cells through the induction of an epigenetic impact. We obtained bone marrow-derived mesenchymal stem cells (BM-MSCs) from mice and collected the conditioned medium (CM) from cultured cells with 90% confluency. The effect of the CM was identified using both 2D and 3D sphere cultures of wild-type human liver cancer cell line (HepG2), considering variations in sphere size and percentage. A cell death study was conducted using the cell cytotoxicity (MTT) kit, while the quantity of stem cells was determined by immunohistochemistry and gene expression analysis. The effectiveness of our therapy was demonstrated by an in vivo assessment of BM-MSCs through intravenous injection and the currently available anticancer drug cisplatin. In vitro, the combination treatment resulted in a synergetic effect, leading to 74% cell death in both adherent and spherical cultures when treated with 25 µM of cisplatin and 90%CM. In vivo, the histological study indicated a decrease in tumor size and number following treatment with cisplatin and BM-MSCs. The study lasted 18 weeks and revealed that the body weight of mice improved across all treatment groups, with the combination group exhibiting the most significant improvement. Both in vitro and in vivo studies showed the synergetic effect of cisplatin and isolated conditioned medium. Our study aimed to identify more efficient therapeutic approaches utilizing stem cells and existing marketed medications to minimize adverse effects with better efficacy.